Psychological Dynamics of Generation Z Employees: The Role of Adjustment in Maintaining Work-Life Balance - Dharma Shanti; Faiz Fatihul 'alwan (Universitas Ahmad Dahlan, 2026)
Work–life balance has become a critical issue in contemporary workplaces, particularly for Generation Z employees who must navigate both work demands and personal-life needs. This study examined whether adjustment predicts work–life balance among Generation Z employees in Indonesia. A quantitative cross-sectional design was used with 269 employees aged 18–27 years. Data were analyzed using simple linear regression. Adjustment significantly predicted WIPL, PLIW, and WEPL, but did not significantly predict PLEW. Overall, the findings suggest that adjustment is more closely linked to reducing inter-role conflict than to enhancing cross-domain enrichment, underscoring the importance of individual adjustment in maintaining work–life balance. Practically, organizations should strengthen Gen Z employees’ adjustment through onboarding, mentoring, and coping-skills training to reduce work–life conflict and support healthier work–life balance.